Density functional theory study of bulk properties of transition metal nitrides. Issue 6 (27th January 2023) - Lynn, Michael O.; Ologunagba, Damilola; Dangi, Beni B.; Kattel, Shyam
Abstract : Bulk properties of transition metal nitrides, an emerging class of materials studied using various DFT exchange and correlation functionals. Abstract : Density functional theory (DFT) calculations are performed to compute the lattice constants, formation energies and vacancy formation energies of transition metal nitrides (TMNs) for transition metals (TM) ranging from 3d–5d series. The results obtained using six different DFT exchange and correlation potentials (LDA, AM05, BLYP, PBE, rPBE, and PBEsol) show that the experimental lattice constants are best predicted by rPBE, while the values obtained using AM05, PBE, rPBE and PBEsol lie between the LDA and BLYP calculated values. A linear relationship is observed between the lattice constants and formation energies with the mean radii of TM and the difference in the electronegativity of TM and N in TMNs, respectively. Our calculated vacancy formation energies, in general, show that N-vacancies are more favorable than TM-vacancies in most TMNs. We observe that N-vacancy formation energies are linearly correlated with the calculated bulk formation energies indicating that TMNs with large negative formation energies are less susceptible to the formation of N-vacancies. Thus, our results from this extensive DFT study not only provide a systematic comparison of various DFT functionals in calculating the properties of TMNs but also serve as reference data for the computation-driven experimental design of materials.